Systematic implications of ocrea morphology in the genus Persicaria (Polygonaceae), focusing on Türkiye - Makbul, Serdar; Kundakçi, Suzan; Coşkunçelebi̇ Kami̇l; Gültepe, Mutlu (Phytotaxa, 2026)
Persicaria (Polygonaceae) is recognized as a taxonomically problematic genus due to the morphological variations. Therefore, additional distinctive characters are needed to classify members of Persicaria. Ocrea is a structure formed by the fusion of stipules, and it is known that ocrea morphology varies among taxa and is of taxonomic importance. Therefore, the study aims to examine the ocrea morphology using the light and scanning electron microscopy of twelve Persicaria taxa distributed in Türkiye. The examinations were conducted on herbarium specimens stored in the Herbarium of the Department of Biology, Recep Tayyip Erdoğan University (RUB). The data obtained showed that ocrea morphology exhibited significant variability among the studied taxa, contributing to the differentiation of these taxa at a specific level. It has been observed that the most important characters contributing to the differentiation of taxa are ocrea length, apex shape, pubescence, epidermal cell shape on the adaxial surface, and the ornamentation of epicuticular wax on both adaxial and abaxial surfaces.